Generic reorganization and nomenclatural synopsis of the Andean Clade (Cleomaceae) - Mcginty, Emma M.; Roalson, Eric H. (Phytotaxa, 2020)
The Andean clade of Cleomaceae is a well-recognized and supported clade in phylogenetic studies, but it is in need of nomenclatural updates. Multiple species have yet to have combinations made for modern generic placement within the clade, particularly those of Cleome species. Here we recognize four genera in the Andean Clade: Andinocleome, Cochranella, Podandrogyne, and Pterocleome. The species Cleome anomala, C. chilensis, C. glandulosa, C. limoneolens, C. longifolia, C. mathewsii, and C. moritziana are considered to belong to Andinocleome. The species Andinocleome pilosa is moved to the monotypic genus Cochranella, and Cleome stylosa is placed in the monotypic genus Pterocleome. We provide nomenclatural updates of genera and species, a key to, and morphological circumscriptions of, the recognized genera, and illustrations of crucial morphological distinctions. A synonymy is included for all species in the three genera treated, excluding Podandrogyne. In total, we treat 11 species and 46 names. Seventeen lectotypes are designated here.